ACCRUAL AND REAL EARNINGS MANAGEMENT THROUGH CASH FLOWS OPERATING ACTIVITY TOWARDS MARKET PERFORMANCE - Hartono, Patricia Vintya Christi; Suganda, Tarsisius Renald; Cahyadi, Sendy (Universitas Brawijaya, Indonesia, 2018)
This research aims to obtain empirical evidence regarding the influence of accrual earnings management and real earnings management through cash flow operating activities towards market performance. The sample is 52 manufacturing's firm listed on the Indonesia Stock Exchange in the period 2012-2016. This study using instrumental variable (IV) models (Kang and Sivaramakrishnan, 1995) to measure accrual earnings management, and using the Roychowdhury's model (2006), to measure real earnings management through cash flow operating activities. Market performance is measured by the cumulative abnormal return (CAR) with market adjusted models. Then, descriptive statistics, one sample t-test, and multiple regression test to test the hypothesis. The results of this research show that there is no negative influence of accrual earnings management with market performance, and there is no positive influence of real earnings management through cash flow operating activities with market performance. Earnings management through accrual and do not affect market performance, because in the longterm period investor have many relevance information apart from financial statements to decide on investment. The suggestions for further research is to explore more about real earning management techniques and consider other factors that might be able to influence market performance on earnings management.